Comparing the community composition of European and Eastern Chinese Waterbirds and the influence of human factors on the China Waterbird Community - Boer, W. Fred de; Cao, L.; Barter, M.; Wang, X.; Sun, M.; Oeveren, H. Van; Leeuw, Jan de; Barzen, J.; Prins, H.H.T. (Springer, 2011)
We compared the European and eastern Chinese waterbird assemblages and checked whether the effects of human disturbance could be detected in the assemblages’ composition. For the different Chinese provinces, we expected to find a negative effect of economic development on the mean bird species mass and on the proportion of bentivorous, piscivorous and insectivorous bird species. We also expected to find relatively fewer large species in the Chinese assemblage. Species rank–abundance curves were relatively similar, but China had significantly more species with smaller body masses. The China assemblage was characterized by relatively higher abundance of heavy-bodied species, contrary to our expectations. Mean bird body mass decreased in China with increasing disturbance and increasing gross domestic product (GDP). For coastal provinces in China the percentage of bentivorous, piscivorous and insectivorous bird species declined with increasing GDP, maybe through the increased use of pesticides or fertilizer.